2016
DOI: 10.3390/ijms17040570
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Plasma miR-215 in Chronic Myeloid Leukemia Patients with Successful Discontinuation of Imatinib

Abstract: Approximately 40% of chronic myeloid leukemia (CML) patients who discontinue imatinib (IM) therapy maintain undetectable minimal residual disease (UMRD) for more than one year (stopping IM (STOP-IM)). To determine a possible biomarker for STOP-IM CML, we examined plasma miRNA expression in CML patients who were able to discontinue IM. We first screened candidate miRNAs in unselected STOP-IM patients, who had sustained UMRD after discontinuing IM for more than six months, in comparison with healthy volunteers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…In this study, we present evidence that long-term exposure to IM, while leading to a significant downregulation of Bcr-Abl1 protein level and its activity, results in inactivation of the Hippo pathway kinase module and upregulation of YAP, and that these changes correlate with increased expression of stem cell markers and acquired insensitivity to IM. Our observations are in agreement with a recent report showing increased levels of miR-181a in the plasma of CML patients who discontinued IM (STOP-IM group) [30]. In the present studies, we have observed that inhibition of miR-181a resulted in a decrease in YAP levels, an increase in its phosphorylation, and a modest but statistically significant increase in sensitivity to IM.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…In this study, we present evidence that long-term exposure to IM, while leading to a significant downregulation of Bcr-Abl1 protein level and its activity, results in inactivation of the Hippo pathway kinase module and upregulation of YAP, and that these changes correlate with increased expression of stem cell markers and acquired insensitivity to IM. Our observations are in agreement with a recent report showing increased levels of miR-181a in the plasma of CML patients who discontinued IM (STOP-IM group) [30]. In the present studies, we have observed that inhibition of miR-181a resulted in a decrease in YAP levels, an increase in its phosphorylation, and a modest but statistically significant increase in sensitivity to IM.…”
supporting
confidence: 94%
“…We focused our subsequent studies on miR-181a as miR-181 family is the most highly conserved and the most preferentially expressed in the hematopoietic system [22,23]. To explore the association of miR-181a upregulation with long-term exposure to IM, we analyzed a published microarray data set: GEO GSE75392; seven CML patients from STOP-IM group and seven healthy volunteers [30]. We found that miR-181a was significantly upregulated in plasma isolated from CML STOP-IM group patients (Fig.…”
Section: Long-term Exposure To Im Results In Increased Levels Of Mir-mentioning
confidence: 99%
“…Exosomal miR-126 in endothelial cells modulates the adhesive and migratory abilities of CML cells [12]. Patients with a low plasma miR-215 expression had a significantly higher total imatinib intake compared to patients with increased miR-215 expression [13]. miR-21 was enriched in exosomes released by K562 and LAMA84 cells after treatment with curcumin, suggesting that selective packaging of miR-21 in the exosomes may contribute to the antileukemic effect of curcumin in CML [14].…”
Section: Research Papermentioning
confidence: 99%
“…Altogether, this supports the notion that leukemic EVs constitute an important mechanism of disease progression both by direct influence on CML cells and by indirect modification of leukemic niche components and immune cells. Moreover, EVs components, such as proteins and microRNAs, have recently become of interest as biomarkers in hematological malignancies [42,48,49]. Thus, analysis of EVs number, size, and composition may soon be used to diagnose, stage, and even analyze relapse of hematological malignancies in the clinical setting.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%